Analisis Surat Keputusan Bersama Tiga Menteri Tentang Peringatan Dan Perintah Kepada penganut, Anggota, Dan/Atau Pengurus Jemaat Ahmadiyah Indonesia - Delina Asriyani; Zulli Qodir (Journal of Governance and Public Policy, 2016)
This thesis discusses the analysis of three Ministers decree on Ahmadiyah (a case study of conflict between FUI and GAIin Yogyakarta, 2012). The ministerial analysis and the factors that cause of conflicts is done by using the theory ofcritical discourse analysis of Norman Fairclough, Antonio Gramsci's theory of hegemony, and the theory of the cause ofconflict by Simon Fisher. From the analysis, it can be concluded that the pros and cons that always arise in the processof production and consumption of three Ministers decree on Ahmadiyah. Groups for Ahmadiyah have opinion thatfreedom must not be restricted because of the position as a citizen. Constitutional guarantees and product legislationrelated to human rights also guarantees it. The group cons have argue that the activities undertaken by the Ahmadiyahis incompatible with Islam. If Ahmadiyah still do the activities, which can not themselves are Muslims. This research alsofound that the factors of causing conflict between FUI and GAI in Yogyakarta, 2012, are not a single. First, the GAI isconsidered an insult to the Muslim faith. Second, straying from MUI to GAI is the main reference for the rejection of GAI.Third, the differences in understanding of the decree about Ahmadiyah. Fourth, the unilateral allegations of each group,and the fifth, the exclusivity of GAI.